Study of Using Mixture of Bintaro and Coconut Shell Charcoal Powder as Pack Carburizing Media on ST 41 Steel - Ridhotullah, Aji; Ashari, Rahmat; Sulistijono, Sulistijono; Andiana, Rocky; Rizky, Yoel (IPTEK Journal of Proceedings Series, 2018)
Pack carburizing is one method of adding carbon into the steel surface. This method is done to improve the mechanical properties of steel so as to reduce the risk of material failure due to static and dynamic load. It has been done in this research about pack carburizing with mixed bintaro charcoal media with coconut shell on ST 41 steel. Carburizing method is done by heating steel which is given a mixture of charcoal at 900 celsius temperature with variation of holding time (1h, 1.5h, 2h) And variation of the charcoal mix ratio with BaCO3 (90: 10, 85: 15, 80: 20). Conducted testing of microstructure, jominy, and the composition so it is known that the mixture of bintaro charcoal and coconut shell quite effectively used as a media pack carburizing. It can be seen that the hardness value of carbon steel has increased with the highest value of 65 HRC, metallographic test results showed good carburizing coating with the best thickness value of 30.9 Âµm, in jominy testing showed the low hardness carbon steel ability increased with the highest distance from the specimen quench-ends about Â¾ inch and on the compositional test results showed an increase in carbon content in steel more than 200%.